Impact of Strengthening Internal Audit’s Roles towards State Budget Loss - Qomaryati, Nurul; Gultom, Yohanna M.L. (JEJAK: Jurnal Ekonomi dan Kebijakan, 2021)
This research evaluates the effect of strengthening government internal audit’s (APIP) roles on reducing state budget loss in Indonesia. Since 2014, the role of internal audit as a provider of objective quality assurance is strengthened by adding comprehensive consulting activities that are inherent in each cycle of state budget process to make sure that there are no irregularities on managing the stage budget. By using the difference-in-differences (DID) approach, this study analyzes state budget loss data obtained from the Audit Board of Republic of Indonesia (BPK) in 492 cities/districts during 2009-2018. The results show that strengthening internal audit’s roles decreased state budget losses in the regions that have a relatively high capital expenditure by 0.435% and it is significant at 1% level. This finding shows the positive effect of adding a consulting role to government internal audit on reducing the state budget losses in Indonesia.